2021
DOI: 10.1177/00187208211037465
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing the Benefits of Participatory Design for Human–Robot Interaction Research With Older Adults

Abstract: Objective We reviewed human–robot interaction (HRI) participatory design (PD) research with older adults. The goal was to identify methods used, determine their value for design of robots with older adults, and provide guidance for best practices. Background Assistive robots may promote aging-in-place and quality of life for older adults. However, the robots must be designed to meet older adults’ specific needs and preferences. PD and other user-centered methods may be used to engage older adults in the robot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 34 publications
1
8
0
1
Order By: Relevance
“…HRI research could also emphasize its active component more strongly. For example, knowledge (on human behavior in HRI contexts) can also be constructed by actively designing human-centered HRI (an approach also known as “research through design”, see Zimmerman et al, 2007 ), while accompanying these activities with critical reflections and documentation ( Lupetti et al, 2021 ) or participatory design ( Rogers et al, 2021 ). For example in work by Gollob et al (2021) , the researchers explored new aesthetic experiences by creating new artefact interactions in different projects.…”
Section: Toward More Reliable Hri Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…HRI research could also emphasize its active component more strongly. For example, knowledge (on human behavior in HRI contexts) can also be constructed by actively designing human-centered HRI (an approach also known as “research through design”, see Zimmerman et al, 2007 ), while accompanying these activities with critical reflections and documentation ( Lupetti et al, 2021 ) or participatory design ( Rogers et al, 2021 ). For example in work by Gollob et al (2021) , the researchers explored new aesthetic experiences by creating new artefact interactions in different projects.…”
Section: Toward More Reliable Hri Researchmentioning
confidence: 99%
“…Similarly, most of the authors of the meta-analyses reported in this article also discussed problems of the original studies and gave several recommendations for future research in their discussion sections (e.g., Leichtmann and Nitsch, 2020a ; Mara et al, 2021 ; Stower et al, 2021 ). Additionally, a growing number of conference workshops on test methods and metrics ( Marvel et al, 2020 ; Marvel et al, 2021 ), on design research ( Luria et al, 2021 ) or ethnography ( Hasse et al, 2018 ) sought to develop new metrics and explored unconventional methodology—endeavors that are also echoed in HRI articles on methods ( Alves-Oliveira et al, 2021 ; Lupetti et al, 2021 ; Rogers et al, 2021 ; Veling and McGinn, 2021 ) or standards ( Fischer, 2021 ; Hoffman and Zhao, 2021 ; Seibt et al, 2021 ). Furthermore, especially the ACM/IEEE International Conference on Human-Robot Interaction emphasized the importance of replication by introducing a theme on “Reproducibility of Human-Robot Interaction” in 2020 and by explicitly calling for submissions of work focusing on replicability of HRI studies in the last few years.…”
Section: Toward More Reliable Hri Researchmentioning
confidence: 99%
“…The results of these questions confirmed the existing literature on the benefits of Participatory Design (PD) workshops (Kafai & Burke, 2016;Rogers, Kadylak, & Bayles, 2021, Akcaoglu, 2014Zin & Yue, 2009;Anderson & Mack, 2019;Moutafidou & Bratitsis, 2018). Likewise, our results regarding PD benefits, and what children do and feel, were validated in the context of newcomer children from Arabic-speaking backgrounds, which has not been studied adequately.…”
Section: Summary Of Analysis and Findings For Research Questionsupporting
confidence: 78%
“…ContraVision complements traditional HFE design and evaluation techniques, for example, cognitive walkthroughs (Mahatody et al, 2010), task analysis methods (Crandall et al, 2006), and Cognitive Work Analysis (Read et al, 2015; Salmon et al, 2016), among others. There has historically been close alignment between HFE and HCI methods, with approaches such as scenario‐based design (Carroll, 1997), design fictions (Brown et al, 2016; Grand & Wiedmer, 2010), participatory design (Rogers et al, 2022), and ideation cards (Lockton et al, 2010; Wetzel et al, 2017) used successfully across both communities to ideate design solutions and explore human interaction with systems. Qualitative methods, like the ContraVision technique, provide a framework for encouraging individuals to think through a proposed concept or design systematically while considering a range of issues.…”
Section: Introductionmentioning
confidence: 99%
“…ContraVision complements traditional HFE design and evaluation techniques, for example, cognitive walkthroughs (Mahatody et al, 2010), task analysis methods (Crandall et al, 2006), and Cognitive Work Analysis (Read et al, 2015;Salmon et al, 2016), among others. There has historically been close alignment between HFE and HCI methods, with approaches such as scenario-based design (Carroll, 1997), design fictions (Brown et al, 2016;Grand & Wiedmer, 2010), participatory design (Rogers et al, 2022), and ideation cards (Lockton et al, 2010;Wetzel et al, 2017)…”
mentioning
confidence: 99%